Nutrition risk and mortality in older oncology patients: An exploratory study. Issue 4 (7th May 2019) - Botero, Liliana; Agarwal, Ekta; Berry, Robyn; Gillespie, Kerri; Isenring, Elisabeth; McCarthy, Alexandra L.
Abstract : Aim: The primary aim of this analysis was to identify if two standard measures incorporated into the comprehensive geriatric assessment; specifically, malnutrition risk and body mass index (BMI), could predict 12‐month mortality in older patients with solid tumours. The secondary aim was to evaluate if malnutrition risk and BMI were associated with chemotherapy outcomes (discontinuation/modification of treatment) in older patients with solid tumours. Methods: Older patients (aged ≥70 years) with solid cancers were recruited from the outpatient oncology clinic of a tertiary hospital in Brisbane, Australia. Participants' nutritional parameters, BMI, and malnutrition risk (determined using the Malnutrition Screening Tool (MST)) were recorded at baseline. Mortality data and chemotherapy outcomes were recorded for 12 months. Results: Seventy‐four participants (67% males, median age 77 (±4.4) years) were recruited. Nearly half the cohort was at‐risk of malnutrition at baseline (n = 39, 46%). Chemotherapy was prescribed to 39% (n = 29) of the cohort. For patients receiving chemotherapy neither being underweight nor having a low or medium risk of malnutrition was associated with adverse chemotherapy outcomes or 12‐month mortality. At a bivariate level, malnutrition risk was significantly associated with 12‐month mortality in patients who did not receive chemotherapy ( P  = 0.018), but not BMI. Conclusions: This analysis indicates that malnutrition risk was a potential indicator of 12‐month mortality in cases where chemotherapy was considered unfeasible. However, this was not an independent risk factor. Further investigation using a larger sample is required to determine the association between malnutrition risk, quality of life and mortality in patients who are not considered to be fit for chemotherapy.